Electrochemical response of co-precipitated and layer-by-layer precipitated hydrous nickel hydroxide and hydrous cobalt hydroxide on platinum in alkaline solutions - Folquer, M. E. (1984)
The voltammetric and open circuit responses of Pt/co-precipitated hydrous nickel and cobalt hydroxides (mixed hydroxide)/electrolyte, Pt/hydrous nickel hydroxide/hydrous cobalt hydroxide (alternate hydroxide)/electrolyte, and Pt/hydrous cobalt hydroxide/hydrous nickel hydroxide (alternate hydroxide)/electrolyte are investigated in 0.1 M KOH at 25 ° C. The co-precipitated hydroxide electrode shows that the presence of hydrous cobalt hydroxide increases the reversibility of the Ni(II)/Ni(III) redox reaction. This behaviour is interpreted in terms of a catalytic effect of the Co(II)/Co(III) reaction on the Ni(II)/Ni(III) reaction through hydroxide ions inserted into the metal hydroxide layer.